2011
DOI: 10.1074/jbc.m111.260273
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Structure of the Signal Peptide Peptidase

Abstract: Signal peptide peptidase (SPP) is an atypical aspartic protease that hydrolyzes peptide bonds within the transmembrane domain of substrates and is implicated in several biological and pathological functions. Here, we analyzed the structure of human SPP by electron microscopy and reconstructed the three-dimensional structure at a resolution of 22 Å . Enzymatically active SPP forms a slender, bullet-shaped homotetramer with dimensions of 85 ؋ 85 ؋ 130 Å . The SPP complex has four concaves on the rhombus-like sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Thus, a detailed structural analysis of the whole ␥-secretase complex is still required. Intriguingly, PSH forms a tetrameric assembly with its N-ter- minal half, which is reminiscent of the single particle analysis data on human SPP (96). The majority of the catalytic site architecture in PSH is formed by its C-terminal half, which is in accordance with the result that the C-terminal portion is the minimal proteolytic core domain of SPP (64).…”
Section: Detailed Structure Of Gxgd Proteasessupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, a detailed structural analysis of the whole ␥-secretase complex is still required. Intriguingly, PSH forms a tetrameric assembly with its N-ter- minal half, which is reminiscent of the single particle analysis data on human SPP (96). The majority of the catalytic site architecture in PSH is formed by its C-terminal half, which is in accordance with the result that the C-terminal portion is the minimal proteolytic core domain of SPP (64).…”
Section: Detailed Structure Of Gxgd Proteasessupporting
confidence: 73%
“…Intriguingly, the recombinant C-terminal half of SPP is sufficient for proteolytic activity in vitro, indicating that this region is the minimal catalytic domain of SPP. We have purified the human SPP protein using the baculovirus/Sf9 cell system and analyzed its structure by single particle analysis (96). Enzymatically active SPP forms a bullet-shaped homotetramer with dimensions of 85 ϫ 85 ϫ 130 Å at 22 Å resolution.…”
Section: Signal Peptide Peptidasementioning
confidence: 99%
“…33,34 Additionally, endogenous DDM-solubilized human and drosophila SPP formed higher molecular weight complexes around 180−200 kDa. 21 We utilized a photolabeling approach to elucidate whether endogenous active SPP is a homodimer or monomer. We synthesized JC10, a photoprobe structurally similar to JC8 except with the addition of a disulfide bond in the biotin linker that can be eluted from the streptavidin matrix with the reducing agent TCEP (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…AtSPP-GFP migrated at a size smaller than 65 kDa, whereas HsSPP-GFP migrated at a size more than 72 kDa. While the reasons underlying this anomalous migration remain to be elucidated, previous Blue Native Polyacrylamide Gel Electrophoresis (BN-PAGE) studies have shown that HsSPP forms a high molecular mass complex under DDM-solubilized conditions [23]. HsSPP and AtSPP may assemble into complexes of different molecular masses.…”
Section: Resultsmentioning
confidence: 99%